Telaprevir for Previously Untreated Chronic Hepatitis C Virus Infection - Jacobson, Ira M; McHutchison, John G; Dusheiko, Geoffrey; Di Bisceglie, Adrian M; Reddy, K. Rajender; Bzowej, Natalie H; Marcellin, Patrick; Muir, Andrew J; Ferenci, Peter; Flisiak, Robert; George, Jacob; George, Shelley; et al. (The New England journal of medicine, 2011)
In patients with HCV infection and no previous treatment, the addition of telaprevir to peginterferon–ribavirin resulted in higher response rates than those achieved with peginterferon–ribavirin alone. High rates of response were achieved with only 24 weeks of treatment. Patients with chronic hepatitis C virus (HCV) infection are at risk for progressive hepatic fibrosis, cirrhosis, portal hypertension, hepatic failure, and hepatocellular carcinoma. 1 – 4 For the past decade, treatment with pegylated interferon (peginterferon alfa) and ribavirin has been associated with rates of sustained virologic response of 40 to 50% among patients with HCV genotype 1 who had received no previous treatment. 5 – 7 At least 48 weeks of treatment is required for most of these patients, and toxic effects may limit the extent of treatment in some patients. 5 – 7 Telaprevir, a linear peptidomimetic HCV NS3/4A serine protease inhibitor, was associated with . . .